Histone Ubiquitination and Deubiquitination in Transcription, DNA Damage Response, and Cancer - Cao, Jian; Yan, Qin (Frontiers in Oncology, 2012)
Histone post-transcriptional modifications play essential roles in regulation of all DNA related processes. Among them, histone ubiquitination has been discovered for more than three decades. However, its functions are still less well understood than other histone modifications such as methylation and acetylation. In this review, we will summarize our current understanding of histone ubiquitination and deubiquitination. In particular, we will focus on how they are regulated by histone ubiquitin ligases and deubiquitinating enzymes. We will then discuss the roles of histone ubiquitination in transcription and DNA damage response and the crosstalk between histone ubiquitination and other histone modifications. Finally, we will review the important roles of histone ubiquitination in stem cell biology and cancer.